Automatización y Control de un invernadero experimental para mejorar su eficiencia energética. - Suárez Vinueza, Rommel Eusebio (2021)
In this thesis project several techniques studied throughout the student life are applied; which are innovative and of great help for people who are dedicated to agriculture. With the application of the necessary techniques and equipment, it is desired to implement an automated greenhouse irrigation system. Which was carried out with the aim of avoiding a waste of the water resource such as water, and with it, expand the production area under irrigation, and with it generate new production options, to contribute to the sovereignty of the population located in the central area of the country through the use of technology. Agriculture currently has market demands in terms of the quality of its products, so it must comply with the market demands in search of economic and environmental sustainability of agricultural production. The focus of the study will be of great help for the care of plants, preventing crops from contracting different pests, diseases, insects, weeds, etc. Automation techniques were used to correctly monitor and control variables such as: Temperature, internal and external humidity respectively.